High-molecular composite material with excellent wear resistance for electric automobile cable and preparation process of high-molecular composite material
By using polymer composite materials such as wear-resistant polyethylene in electric vehicle cables, the problem of insufficient wear resistance of electric vehicle cables is solved, significantly improving wear resistance and service life, and ensuring that the cable is in a high-strength environment. Stable operation.
Patent Information
- Application Number
- CN202411480525.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-10
AI Technical Summary
The existing electric vehicle cables are not wear-resistant, resulting in the risk of aging of insulation, cracks and short-circuits, which cannot meet the needs of long-term operation of electric vehicles.
Using wear-resistant polyethylene, nanomontmorillonite, aluminum hydroxide, zinc stearate, polyethylene wax, antioxidant 168 and light stabilizer 770, polymer composite materials are melt-extruded through a twin-screw extruder , and prepared polymer composite materials for electric vehicle cables with excellent wear resistance.
It significantly improves the wear resistance of electric vehicle cables, extends service life, reduces the risk of aging and damage, ensures stable and reliable transmission of power in high-strength environments, and improves safety.
Smart Images

Figure CN119286095A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of cable materials, and in particular to a polymer composite material for electric vehicle cables with excellent wear resistance and a preparation process thereof. Background Art
[0002] With the rapid development of electric vehicles, higher and higher requirements are placed on the reliability and wear resistance of power battery power supply lines. Existing electric vehicle cables mainly use copper wire or aluminum wire as conductors, and use materials such as rubber or polyethylene as insulation layers. Although these materials have certain satisfaction in service life and performance, their wear resistance is still insufficient, resulting in frequent friction of electric vehicle cables during the use of electric vehicles, leading to aging, cracking, and even short circuit risks of the insulation layer, which cannot meet the needs of long-term operation of electric vehicles. Therefore, it is of great significance to develop a polymer composite material and preparation process for electric vehicle cables with excellent wear resistance. Summary of the invention
[0003] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a polymer composite material for electric vehicle cables with excellent wear resistance and a preparation process. The wear-resistant polyethylene, nano-montmorillonite, aluminum hydroxide, zinc stearate, polyethylene wax, antioxidant 168 and light stabilizer 770 are mixed evenly, and then melt-extruded and granulated through a twin-screw extruder to obtain a polymer composite material for electric vehicle cables with excellent wear resistance, which solves the problem that the existing polymer composite materials for electric vehicle cables have poor wear resistance and cannot meet the needs of long-term operation of electric vehicles.
[0004] The purpose of the present invention can be achieved through the following technical solutions: A polymer composite material for electric vehicle cables with excellent wear resistance, comprising the following components in parts by weight: Wear-resistant polyethylene 82-96 parts, nano-montmorillonite 11-23 parts, aluminum hydroxide 3-9 parts, zinc stearate 2-4.8 parts, polyethylene wax 1-3 parts, antioxidant 168 0.5-0.9 parts and light stabilizer 770 0.2-0.6 parts; Wherein, the wear-resistant polyethylene is prepared by the following steps: Step s1: polyvinyl pyrrolidone and anhydrous ethanol are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred and reacted for 20-30 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min. Then, yttrium nitrate hexahydrate, zirconium n-propoxide and acetylacetone are added and the mixture is heated to 40-45° C. and stirred and reacted for 10-15 hours. After the reaction is completed, the reaction product is cooled to room temperature to obtain a spinning solution. Step s2: electrospinning the spinning solution under the conditions of humidity of 30-40%, temperature of 15-25°C and spinning voltage of 15-20kV, then placing the formed fiber membrane in a vacuum drying oven, drying at a temperature of 60-65°C for 2-3h, then placing it in a tubular furnace, introducing argon protection, and heating to 600-620°C at a heating rate of 1-1.5°C / min, then heat treating at a constant temperature for 2-2.5h, then heating to 900-1100°C at a heating rate of 5-6°C / min, then heat treating at a constant temperature for 1-1.5h, and then cooling with the furnace to obtain wear-resistant reinforced fiber; Step s3: adding perfluorohexylethanol, chloroacrylic acid, p-toluenesulfonic acid and hydroquinone into a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introducing nitrogen protection, stirring the reaction at a temperature of 20-25° C. and a stirring rate of 300-400 r / min for 1-2 hours, then heating to 145-150° C. and continuing to stir the reaction for 2-3 hours. After the reaction is completed, the reaction product is cooled to room temperature, then washed with saturated brine for 2-3 times, then allowed to stand for stratification, and the organic phase is dried over anhydrous sodium sulfate, and then vacuum filtered to obtain an intermediate; Step s4: adding the intermediate, γ-aminopropyltriethoxysilane, hydroquinone and toluene into a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introducing nitrogen protection, stirring the reaction at a temperature of 20-25°C and a stirring rate of 300-400r / min for 1-2h, then heating the temperature to 60-65°C and continuing to stir the reaction for 4-5h, then adding triethylamine and heating the temperature to 80-85°C and continuing to stir the reaction for 1-2h, after the reaction is completed, cooling the reaction product to room temperature, then vacuum filtering, and rotary evaporating the filtrate to remove the solvent to obtain a fiber reinforcement; Step s5: adding the wear-resistant reinforcing fiber, the fiber reinforcement and the ethanol solution into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introducing nitrogen protection, stirring the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heating to 70-75°C and continuing to stir the reaction for 6-8 hours, and after the reaction is completed, cooling the reaction product to room temperature, and then vacuum filtering, washing the filter cake with toluene and methanol for 2-3 times in turn, and then placing it in a vacuum drying oven, and drying it at a temperature of 50-55°C for 1-1.5 hours to obtain a modified wear-resistant reinforcing fiber; Step s6: Add low-density polyethylene, OP-10 surfactant, toluene and deionized water into a three-necked flask equipped with an agitator, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 5-10 minutes at a temperature of 20-25°C and a stirring rate of 300-400r / min, then heat to 70-75°C and continue to stir and react for 30-40 minutes, then add modified wear-resistant reinforcing fiber and benzoyl peroxide and heat to 85-90°C and continue to stir and react for 4-5 hours, after the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with acetone 2-3 times, then place it in a vacuum drying oven, and dry it at a temperature of 50-55°C for 3-5 hours to obtain wear-resistant polyethylene.
[0005] As a further solution of the present invention: the usage ratio of the polyvinyl pyrrolidone, anhydrous ethanol, yttrium nitrate hexahydrate, zirconium n-propoxide and acetylacetone in step s1 is 0.5-0.55g:5.5-6g:0.09-0.11g:1g:0.22-0.26g.
[0006] As a further solution of the present invention: the usage ratio of the perfluorohexylethanol, chloroacrylic acid, p-toluenesulfonic acid and hydroquinone in step s3 is 10 mmol: 10 mmol: 0.03-0.05 g: 0.01-0.02 g.
[0007] As a further solution of the present invention: the usage ratio of the intermediate, γ-aminopropyltriethoxysilane, hydroquinone and toluene in step s4 is 10 mmol: 10 mmol: 0.01-0.03 g: 50-60 mL.
[0008] As a further solution of the present invention: the usage ratio of the wear-resistant reinforcing fiber, the fiber reinforcing agent and the ethanol solution in step s5 is 5g:0.9-3.5g:80-85mL.
[0009] As a further solution of the present invention: the volume fraction of the ethanol solution in step s5 is 85-90%.
[0010] As a further solution of the present invention: the usage ratio of the low-density polyethylene, OP-10 surfactant, toluene, deionized water, modified wear-resistant reinforcing fiber and benzoyl peroxide in step s6 is 20g: 0.01-0.015g: 35-45mL: 35-45mL: 0.8-2.2g: 0.1-0.3g.
[0011] As a further solution of the present invention: the low-density polyethylene in step s6 is Malaysian PETLINLDPEM022X low-density polyethylene.
[0012] As a further solution of the present invention: a process for preparing a polymer composite material for electric vehicle cables with excellent wear resistance comprises the following steps: Step 1: weigh 82-96 parts of wear-resistant polyethylene, 11-23 parts of nano-montmorillonite, 3-9 parts of aluminum hydroxide, 2-4.8 parts of zinc stearate, 1-3 parts of polyethylene wax, 0.5-0.9 parts of antioxidant 168 and 0.2-0.6 parts of light stabilizer 770 according to weight parts, and set aside; Step 2: Evenly mix the wear-resistant polyethylene, nano-montmorillonite, aluminum hydroxide, zinc stearate, polyethylene wax, antioxidant 168 and light stabilizer 770, and then melt-extrude and granulate them through a twin-screw extruder to obtain a polymer composite material for electric vehicle cables with excellent wear resistance.
[0013] Beneficial effects of the present invention: The polymer composite material for electric vehicle cables with excellent wear resistance and the preparation process of the present invention are prepared by uniformly mixing wear-resistant polyethylene, nano-montmorillonite, aluminum hydroxide, zinc stearate, polyethylene wax, antioxidant 168 and light stabilizer 770, and then melt-extruding and granulating the mixture through a twin-screw extruder to obtain the polymer composite material for electric vehicle cables with excellent wear resistance; the preparation process uses wear-resistant polyethylene as the main raw material, effectively improves the wear resistance of the electric vehicle cable, and prolongs the service life, thereby ensuring that the electric vehicle cable can stably and reliably transmit electricity in a high-intensity driving environment, greatly reducing the risk of aging, damage and scrapping of the electric vehicle cable, thereby prolonging the service life of the electric vehicle and improving safety; the preparation process is simple and low-cost, and contributes to the sustainable development of the electric vehicle industry.
[0014] In the process of preparing a polymer composite material for electric vehicle cables with excellent wear resistance, a wear-resistant polyethylene is first prepared. First, yttrium nitrate hexahydrate and zirconium n-propoxide are used as raw materials for spinning and calcination to form yttrium-stabilized zirconia nanofibers to obtain wear-resistant reinforcing fibers. Then, perfluorohexylethanol and chloroacrylic acid are used as raw materials for esterification reaction to obtain an intermediate. Then, the intermediate and γ-aminopropyltriethoxysilane react. The chlorine atoms on the intermediate react with the amino groups on the γ-aminopropyltriethoxysilane to introduce siloxane groups to obtain a fiber reinforcing agent. Then, the wear-resistant reinforcing fibers are treated with the fiber reinforcing agent. After the fiber reinforcing agent is hydrolyzed, the siloxane groups on the fiber reinforcing agent form silanols and are grafted onto the wear-resistant reinforcing fibers to obtain modified wear-resistant reinforcing fibers. Finally, the modified wear-resistant reinforcing fibers are used to graft and blend low-density polyethylene to obtain wear-resistant polyethylene. The yttrium-stabilized zirconia fiber has high hardness and wear resistance. Therefore, blending the wear-resistant reinforcing fibers into the polyethylene matrix can significantly improve the wear resistance of the composite material, and after being treated with the fiber reinforcement agent, the dispersibility of the wear-resistant reinforcing fibers can be greatly improved, so that they can be well compatible with the polyethylene matrix, and the performance of the polyethylene matrix is most significantly enhanced. The molecular structure of the fiber reinforcement agent also contains olefin groups. Polyethylene forms free radicals under the initiation of benzoyl peroxide, which can undergo a grafting reaction with the olefin groups, so that the wear-resistant reinforcing fibers are compatible with the polyethylene matrix in the form of chemical bonds, and their reinforcing performance is further improved. At the same time, the molecular structure of the fiber reinforcement agent also contains a large number of CF bonds. The CF bonds have low surface energy and show good lubricity. They can form a layer of physical adsorption film with a low friction coefficient, which can effectively reduce the direct contact between the friction pairs, thereby reducing friction and wear, and further significantly improving their wear resistance. DETAILED DESCRIPTION
[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] Embodiment 1: This embodiment is a preparation process of a polymer composite material for electric vehicle cables with excellent wear resistance, comprising the following steps: Step 1: Add 0.5g polyvinyl pyrrolidone and 5.5g anhydrous ethanol into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 20min at a temperature of 25°C and a stirring rate of 300r / min, then add 0.09g yttrium nitrate hexahydrate, 1g zirconium n-propoxide and 0.22g acetylacetone, and continue stirring and reacting for 10h under the condition of heating to 40°C. After the reaction is completed, cool the reaction product to room temperature to obtain a spinning solution; Step 2: electrospin the spinning solution under the conditions of humidity of 30%, temperature of 15°C and spinning voltage of 15kV, then place the formed fiber membrane in a vacuum drying oven, dry it at a temperature of 60°C for 2h, then place it in a tubular furnace, introduce argon protection, and heat it to 600°C at a heating rate of 1°C / min, then heat it at a constant temperature for 2h, then heat it to 900°C at a heating rate of 5°C / min, then heat it at a constant temperature for 1h, and then cool it with the furnace to obtain wear-resistant reinforced fiber; Step 3: 10 mmol perfluorohexylethanol, 10 mmol chloroacrylic acid, 0.03 g p-toluenesulfonic acid and 0.01 g hydroquinone are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 20° C. and a stirring rate of 300 r / min for 1 hour, and then the mixture is heated to 145° C. and stirred for 2 hours. After the reaction is completed, the reaction product is cooled to room temperature, washed twice with saturated brine, and then allowed to stand for stratification. The organic phase is dried over anhydrous sodium sulfate, and then vacuum filtered to obtain an intermediate; Step 4: 10 mmol of the intermediate, 10 mmol of γ-aminopropyltriethoxysilane, 0.01 g of hydroquinone and 50 mL of toluene were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 20°C and a stirring rate of 300 r / min for 1 hour, and then the mixture was heated to 60°C and stirred for 4 hours. After that, triethylamine was added and the mixture was heated to 80°C and stirred for 1 hour. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filtrate was rotary evaporated to remove the solvent to obtain a fiber reinforcement. Step 5: Add 5g of wear-resistant reinforcing fiber, 0.9g of fiber reinforcement and 80mL of ethanol solution with a volume fraction of 85% to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 20min at a temperature of 25°C and a stirring rate of 300r / min, then heat to 70°C and continue stirring and reacting for 6h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed twice with toluene and methanol in sequence, and then placed in a vacuum drying oven and dried at a temperature of 50°C for 1h to obtain a modified wear-resistant reinforcing fiber; Step six: 20g of Malaysian PETLINLDPE M022X low-density polyethylene, 0.01g of OP-10 surfactant, 35mL of toluene and 35mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen was introduced for protection. The reaction was stirred for 5 minutes at a temperature of 20°C and a stirring rate of 300r / min, and then the temperature was raised to 70°C and the stirring reaction was continued for 30 minutes. Then, 0.8g of modified wear-resistant reinforcing fiber and 0.1g of benzoyl peroxide were added and the temperature was raised to 85°C and the stirring reaction was continued for 4 hours. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with acetone twice, and then placed in a vacuum drying oven and dried at a temperature of 50°C for 3 hours to obtain wear-resistant polyethylene; Step 7: Weigh 82 parts of wear-resistant polyethylene, 11 parts of nano-montmorillonite, 3 parts of aluminum hydroxide, 2 parts of zinc stearate, 1 part of polyethylene wax, 0.5 parts of antioxidant 168 and 0.2 parts of light stabilizer 770 according to weight parts, and set aside; Step 8: The wear-resistant polyethylene, nano-montmorillonite, aluminum hydroxide, zinc stearate, polyethylene wax, antioxidant 168 and light stabilizer 770 are mixed evenly, and then melt-extruded and granulated through a twin-screw extruder to obtain a polymer composite material for electric vehicle cables with excellent wear resistance.
[0017] Embodiment 2: This embodiment is a preparation process of a polymer composite material for electric vehicle cables with excellent wear resistance, comprising the following steps: Step 1: Add 0.52g polyvinyl pyrrolidone and 5.8g anhydrous ethanol into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 25min at a temperature of 28°C and a stirring rate of 350r / min, then add 0.1g yttrium nitrate hexahydrate, 1g zirconium n-propoxide and 0.24g acetylacetone, and continue stirring and reacting for 12h under the condition of heating to 42°C. After the reaction, cool the reaction product to room temperature to obtain a spinning solution; Step 2: electrospin the spinning solution under the conditions of humidity of 35%, temperature of 20°C and spinning voltage of 18kV, then place the formed fiber membrane in a vacuum drying oven, dry it at a temperature of 62°C for 2.5h, then place it in a tubular furnace, pass argon gas protection, and heat it to 610°C at a heating rate of 1.2°C / min, then heat treat it at a constant temperature for 2h, then heat it to 1000°C at a heating rate of 5.5°C / min, then heat treat it at a constant temperature for 1.5h, and then cool it with the furnace to obtain wear-resistant reinforced fiber; Step 3: 10 mmol perfluorohexylethanol, 10 mmol chloroacrylic acid, 0.04 g p-toluenesulfonic acid and 0.015 g hydroquinone were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The reaction was stirred at a temperature of 22° C. and a stirring rate of 350 r / min for 1.5 h, and then the temperature was raised to 148° C. and the stirring reaction was continued for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then washed twice with saturated brine, and then allowed to stand for stratification. The organic phase was dried over anhydrous sodium sulfate, and then vacuum filtered to obtain an intermediate; Step 4: Add 10 mmol of the intermediate, 10 mmol of γ-aminopropyltriethoxysilane, 0.02 g of hydroquinone and 55 mL of toluene to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction at a temperature of 22° C. and a stirring rate of 350 r / min for 1.5 h, then heat the temperature to 62° C. and continue to stir the reaction for 4.5 h, then add triethylamine and heat the temperature to 82° C. and continue to stir the reaction for 1.5 h. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain a fiber reinforcement; Step 5: Add 5g of wear-resistant reinforcing fiber, 2.2g of fiber reinforcement and 83mL of ethanol solution with a volume fraction of 88% to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 25min at a temperature of 28°C and a stirring rate of 350r / min, then continue to stir and react for 7h at a temperature of 72°C, and after the reaction is completed, cool the reaction product to room temperature, and then vacuum filter, wash the filter cake with toluene and methanol twice in sequence, and then place it in a vacuum drying oven and dry it at a temperature of 52°C for 1h to obtain a modified wear-resistant reinforcing fiber; Step six: 20g of Malaysian PETLINLDPE M022X low-density polyethylene, 0.012g of OP-10 surfactant, 40mL of toluene and 40mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen was introduced for protection. The reaction was stirred for 8 minutes at a temperature of 22°C and a stirring rate of 350r / min, and then the temperature was raised to 72°C and the stirring reaction was continued for 35 minutes. Then, 1.5g of modified wear-resistant reinforcing fiber and 0.2g of benzoyl peroxide were added and the temperature was raised to 88°C and the stirring reaction was continued for 4.5h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed twice with acetone, and then placed in a vacuum drying oven and dried at a temperature of 52°C for 4h to obtain wear-resistant polyethylene; Step 7: Weigh 89 parts of wear-resistant polyethylene, 17 parts of nano-montmorillonite, 6 parts of aluminum hydroxide, 3.4 parts of zinc stearate, 2 parts of polyethylene wax, 0.7 parts of antioxidant 168 and 0.4 parts of light stabilizer 770 according to weight parts, and set aside; Step 8: The wear-resistant polyethylene, nano-montmorillonite, aluminum hydroxide, zinc stearate, polyethylene wax, antioxidant 168 and light stabilizer 770 are mixed evenly, and then melt-extruded and granulated through a twin-screw extruder to obtain a polymer composite material for electric vehicle cables with excellent wear resistance.
[0018] Embodiment 3: This embodiment is a preparation process of a polymer composite material for electric vehicle cables with excellent wear resistance, comprising the following steps: Step 1: Add 0.55g polyvinyl pyrrolidone and 6g anhydrous ethanol into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 30min at a temperature of 30°C and a stirring rate of 400r / min, then add 0.11g yttrium nitrate hexahydrate, 1g zirconium n-propoxide and 0.26g acetylacetone, and continue stirring and reacting for 15h under the condition of heating to 45°C. After the reaction is completed, cool the reaction product to room temperature to obtain a spinning solution; Step 2: electrospin the spinning solution under the conditions of humidity of 40%, temperature of 25°C and spinning voltage of 20kV, then place the formed fiber membrane in a vacuum drying oven, dry it at a temperature of 65°C for 3h, then place it in a tubular furnace, pass argon gas protection, and heat it to 620°C at a heating rate of 1.5°C / min, then heat treat it at a constant temperature for 2.5h, then heat it to 1100°C at a heating rate of 6°C / min, then heat treat it at a constant temperature for 1.5h, and then cool it with the furnace to obtain wear-resistant reinforced fiber; Step 3: 10 mmol perfluorohexylethanol, 10 mmol chloroacrylic acid, 0.05 g p-toluenesulfonic acid and 0.02 g hydroquinone are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 2 h, and then the mixture is heated to 150° C. and stirred for reaction for 3 h. After the reaction is completed, the reaction product is cooled to room temperature, and then washed with saturated brine for 3 times, and then allowed to stand for stratification. The organic phase is dried over anhydrous sodium sulfate, and then vacuum filtered to obtain an intermediate; Step 4: Add 10 mmol of the intermediate, 10 mmol of γ-aminopropyltriethoxysilane, 0.03 g of hydroquinone and 60 mL of toluene to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, introduce nitrogen protection, stir and react for 2 hours at a temperature of 25°C and a stirring rate of 400 r / min, then continue to stir and react for 5 hours at a temperature of 65°C, then add triethylamine and continue to stir and react for 2 hours at a temperature of 85°C. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain a fiber reinforcement; Step 5: Add 5g of wear-resistant reinforcing fiber, 3.5g of fiber reinforcement and 85mL of 90% ethanol solution by volume to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 30min at a temperature of 30°C and a stirring rate of 400r / min, then heat to 75°C and continue stirring and reacting for 8h. After the reaction, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with toluene and methanol three times in sequence, then place it in a vacuum drying oven, and dry it at a temperature of 55°C for 1.5h to obtain modified wear-resistant reinforcing fiber; Step six: 20g of Malaysian PETLINLDPE M022X low-density polyethylene, 0.015g of OP-10 surfactant, 45mL of toluene and 45mL of deionized water were added to a three-necked flask equipped with an agitator, a thermometer, an air duct and a reflux condenser, and nitrogen was introduced for protection. The reaction was stirred for 10 minutes at a temperature of 25°C and a stirring rate of 400r / min, and then the temperature was raised to 75°C and the stirring reaction was continued for 40 minutes. Then, 2.2g of modified wear-resistant reinforcing fiber and 0.3g of benzoyl peroxide were added and the temperature was raised to 90°C and the stirring reaction was continued for 5 hours. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with acetone 3 times, and then placed in a vacuum drying oven and dried at a temperature of 55°C for 5 hours to obtain wear-resistant polyethylene; Step 7: Weigh 96 parts of wear-resistant polyethylene, 23 parts of nano-montmorillonite, 9 parts of aluminum hydroxide, 4.8 parts of zinc stearate, 3 parts of polyethylene wax, 0.9 parts of antioxidant 168 and 0.6 parts of light stabilizer 770 according to weight parts, and set aside; Step 8: The wear-resistant polyethylene, nano-montmorillonite, aluminum hydroxide, zinc stearate, polyethylene wax, antioxidant 168 and light stabilizer 770 are mixed evenly, and then melt-extruded and granulated through a twin-screw extruder to obtain a polymer composite material for electric vehicle cables with excellent wear resistance.
[0019] Comparative Example 1: This comparative example is a preparation process of a polymer composite material for electric vehicle cables with excellent wear resistance, comprising the following steps: Step 1: Weigh 96 parts of maleic PETLINLDPE M022X low-density polyethylene, 23 parts of nano-montmorillonite, 9 parts of aluminum hydroxide, 4.8 parts of zinc stearate, 3 parts of polyethylene wax, 0.9 parts of antioxidant 168 and 0.6 parts of light stabilizer 770 according to weight parts, and set aside; Step 2: Evenly mix the Malaysian PETLINLDPE M022X low-density polyethylene, nano-montmorillonite, aluminum hydroxide, zinc stearate, polyethylene wax, antioxidant 168 and light stabilizer 770, and then melt-extrude and granulate them through a twin-screw extruder to obtain a polymer composite material for electric vehicle cables with excellent wear resistance.
[0020] Comparative Example 2: This comparative example is a preparation process of a polymer composite material for electric vehicle cables with excellent wear resistance, comprising the following steps: Step 1: Add 0.55g polyvinyl pyrrolidone and 6g anhydrous ethanol into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 30min at a temperature of 30°C and a stirring rate of 400r / min, then add 0.11g yttrium nitrate hexahydrate, 1g zirconium n-propoxide and 0.26g acetylacetone, and continue stirring and reacting for 15h under the condition of heating to 45°C. After the reaction is completed, cool the reaction product to room temperature to obtain a spinning solution; Step 2: electrospin the spinning solution under the conditions of humidity of 40%, temperature of 25°C and spinning voltage of 20kV, then place the formed fiber membrane in a vacuum drying oven, dry it at a temperature of 65°C for 3h, then place it in a tubular furnace, pass argon gas protection, and heat it to 620°C at a heating rate of 1.5°C / min, then heat treat it at a constant temperature for 2.5h, then heat it to 1100°C at a heating rate of 6°C / min, then heat treat it at a constant temperature for 1.5h, and then cool it with the furnace to obtain wear-resistant reinforced fiber; Step 3: Add 5g of wear-resistant reinforcing fiber, 3.5g of γ-aminopropyltriethoxysilane and 85mL of 90% ethanol solution by volume to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 30min at a temperature of 30°C and a stirring rate of 400r / min, then continue to stir and react for 8h under the condition of heating to 75°C, and after the reaction is completed, cool the reaction product to room temperature, and then vacuum filter, wash the filter cake with toluene and methanol three times in sequence, and then place it in a vacuum drying oven, and dry it at a temperature of 55°C for 1.5h to obtain a modified wear-resistant reinforcing fiber; Step 4: 20g of Malaysian PETLINLDPE M022X low-density polyethylene, 0.015g of OP-10 surfactant, 45mL of toluene and 45mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen was introduced for protection. The reaction was stirred for 10 minutes at a temperature of 25°C and a stirring rate of 400r / min, and then the temperature was raised to 75°C and the stirring reaction was continued for 40 minutes. Then, 2.2g of modified wear-resistant reinforcing fiber and 0.3g of benzoyl peroxide were added and the temperature was raised to 90°C and the stirring reaction was continued for 5h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with acetone 3 times, and then placed in a vacuum drying oven and dried at a temperature of 55°C for 5h to obtain wear-resistant polyethylene; Step 5: Weigh 96 parts of wear-resistant polyethylene, 23 parts of nano-montmorillonite, 9 parts of aluminum hydroxide, 4.8 parts of zinc stearate, 3 parts of polyethylene wax, 0.9 parts of antioxidant 168 and 0.6 parts of light stabilizer 770 according to weight parts, and set aside; Step six: evenly mix the wear-resistant polyethylene, nano-montmorillonite, aluminum hydroxide, zinc stearate, polyethylene wax, antioxidant 168 and light stabilizer 770, and then melt-extrude and granulate them through a twin-screw extruder to obtain a polymer composite material for electric vehicle cables with excellent wear resistance.
[0021] The polymer composite materials for electric vehicle cables with excellent wear resistance of Examples 1-3 and Comparative Examples 1-2 were pressed into discs with a thickness of 10 mm and a diameter of 10 mm. The discs were dry rubbed for 2 h at a speed of 200 r / min and a load of 200 N to test their wear resistance. The test results are shown in the following table:
[0022] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-2, it can be known that the wear-resistant polymer composite material for electric vehicle cables of the present application has excellent wear resistance.
[0023] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0024] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A polymer composite material for electric vehicle cables having excellent wear resistance, characterized in that: It includes the following components by weight: Wear-resistant polyethylene 82-96 parts, nano-montmorillonite 11-23 parts, aluminum hydroxide 3-9 parts, zinc stearate 2-4.8 parts, polyethylene wax 1-3 parts, antioxidant 168 0.5-0.9 parts and light stabilizer 770 0.2-0.6 parts; Wherein, the wear-resistant polyethylene is prepared by the following steps: Step s1: stirring polyvinyl pyrrolidone and anhydrous ethanol for reaction, then adding yttrium nitrate hexahydrate, zirconium n-propoxide and acetylacetone and continuing stirring for reaction, and cooling the reaction product after the reaction is completed to obtain a spinning solution; Step s2: electrospinning the spinning solution, drying the formed fiber membrane, heat treating it at a constant temperature, and then cooling it in the furnace to obtain the wear-resistant reinforced fiber; Step s3: stirring perfluorohexylethanol, chloroacrylic acid, p-toluenesulfonic acid and hydroquinone for reaction, cooling the reaction product after the reaction is completed, then washing with saturated brine, then standing to separate, drying the organic phase with anhydrous sodium sulfate, and then vacuum filtering to obtain an intermediate; Step s4: stirring the intermediate, γ-aminopropyltriethoxysilane, hydroquinone and toluene for reaction, then adding triethylamine and continuing stirring for reaction, cooling the reaction product after the reaction is completed, then vacuum filtering, and rotary evaporating the filtrate to obtain a fiber reinforcement; Step s5: stirring the wear-resistant reinforcing fiber, the fiber reinforcing agent and the ethanol solution to react, cooling the reaction product after the reaction is completed, and then vacuum filtering, washing the filter cake with toluene and methanol in turn, and then drying to obtain the modified wear-resistant reinforcing fiber; Step s6: stirring the low-density polyethylene, OP-10 surfactant, toluene and deionized water to react, then adding the modified wear-resistant reinforcing fiber and benzoyl peroxide to continue stirring the reaction, cooling the reaction product after the reaction is completed, then vacuum filtering, washing the filter cake with acetone, and then drying to obtain wear-resistant polyethylene.
2. The polymer composite material for electric vehicle cables having excellent wear resistance according to claim 1, characterized in that: The usage ratio of the polyvinyl pyrrolidone, anhydrous ethanol, yttrium nitrate hexahydrate, zirconium n-propoxide and acetylacetone in step s1 is 0.5-0.55g:5.5-6g:0.09-0.11g:1g:0.22-0.26g.
3. The polymer composite material for electric vehicle cables having excellent wear resistance according to claim 1, characterized in that: The usage ratio of the perfluorohexylethanol, chloroacrylic acid, p-toluenesulfonic acid and hydroquinone in step s3 is 10 mmol: 10 mmol: 0.03-0.05 g: 0.01-0.02 g.
4. The polymer composite material for electric vehicle cables having excellent wear resistance according to claim 1, characterized in that: The usage ratio of the intermediate, γ-aminopropyltriethoxysilane, hydroquinone and toluene in step s4 is 10 mmol: 10 mmol: 0.01-0.03 g: 50-60 mL.
5. The polymer composite material for electric vehicle cables having excellent wear resistance according to claim 1, characterized in that: The usage ratio of the wear-resistant reinforcing fiber, the fiber reinforcing agent and the ethanol solution in step s5 is 5g:0.9-3.5g:80-85mL.
6. The polymer composite material for electric vehicle cables having excellent wear resistance according to claim 1, characterized in that: The volume fraction of the ethanol solution in step s5 is 85-90%.
7. The polymer composite material for electric vehicle cables having excellent wear resistance according to claim 1, characterized in that: The usage ratio of the low-density polyethylene, OP-10 surfactant, toluene, deionized water, modified wear-resistant reinforcing fiber and benzoyl peroxide in step s6 is 20g: 0.01-0.015g: 35-45mL: 35-45mL: 0.8-2.2g: 0.1-0.3g.
8. The polymer composite material for electric vehicle cables having excellent wear resistance according to claim 1, characterized in that: The low-density polyethylene in step s6 is Malaysian PETLINLDPE M022X low-density polyethylene.
9. A process for preparing a polymer composite material for electric vehicle cables having excellent wear resistance, characterized in that: The following steps are involved: Step 1: weigh 82-96 parts of wear-resistant polyethylene, 11-23 parts of nano-montmorillonite, 3-9 parts of aluminum hydroxide, 2-4.8 parts of zinc stearate, 1-3 parts of polyethylene wax, 0.5-0.9 parts of antioxidant 168 and 0.2-0.6 parts of light stabilizer 770 according to weight parts, and set aside; Step 2: Evenly mix the wear-resistant polyethylene, nano-montmorillonite, aluminum hydroxide, zinc stearate, polyethylene wax, antioxidant 168 and light stabilizer 770, and then melt-extrude and granulate them through a twin-screw extruder to obtain a polymer composite material for electric vehicle cables with excellent wear resistance.